Slavic Dragon and Nordic Germanic Troll as Figural Variants of the Antagonist from Different Cultures - Pažitná, Bernadette (Slavia Centralis, 2024)
The study with a thematological analytical-comparative methodological platform focuses on two significant and motif-related types of the villain (Propp 2008) character/function – Slavic dragon and Nordic-Germanic troll. They are the two most frequent figural variants of fairytale-mythological antagonists from European stories and chosen cultural-civilizational circles, not only in myths but particularly in fairy tales, which, according to AarneThompson-Uther international catalog of tale types, are marked as 301 The Three Stolen Princesses.